Practical Implementation of the Principles - Constituents of the Rule of Law in Civil Relations - Butryn-Boka, Nataliia; Parashchuk, Liliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article deals with the research of issues related to the implementation of the rule of law principle in civil relations. The authors reveal the peculiarities of the implementation of the principles - components of the rule of law in certain institutions of civil law. The rule of law is one of the fundamental principles not only of lawmaking but also of law enforcement. The complexity and versatility of this phenomenon necessitates its disclosure in relation to other legal principles that exist as its component. Among the principles there are constituents of the rule of law, as defined by the Venice Commission in the Rule of Law Checklist, the principles of subsidiary, proportionality, legal certainty, equality before the law, etc. These principles have their own peculiarities of implementation in civil legal relations. Therefore, the principle of subsidiary is a guarantor of personal freedom and a requirement for state institutions to recognize the priority of human rights and interests. The principle of proportionality is a requirement for authorities not to impose on citizens obligations that go beyond the limits of public necessity, and to take maximum account of private interests; setting goals and choosing the means to achieve them, to maximize the possible consequences of such actions. This principle is actualized in property relations, since the exercise of property rights is an important means of realizing personality. The principle of popular sovereignty in action creates the preconditions for self-realization of the population, the existence of mutually beneficial relations between legally equal, independently independent, autonomous subjects of private legal relations. The principle of legal certainty in civil legal relationships is implemented through the requirement of civil law to meet the criteria of accessibility, predictability, sustainability and consistency of legal requirements. The value of this principle lies in legal certainty, the protection afforded by all parties to a civil legal relationship, provided that the state respects that principle. The principle of equality before the law is implemented in civil law by ensuring the formal equality of virtually unequal subjects, impartial reconciliation of interests. Equality before the law, non-discrimination is a requirement of anti-discrimination legislation, guaranteeing the prescriptions of the right of non-discrimination.